Latin and Arabic Entangled Histories - König, Daniel G. (Heidelberg Studies on Transculturality, 2019)
As linguistic systems comprising a large variety of written and oral registers including derivate "languages" and "dialects," Latin and Arabic have been of paramount importance for the history of the Euromediterranean since Antiquity. Moreover, due to their long-term function as languages of administration, intellectual activity, and religion, they are often regarded as cultural markers of Europe and the (Arabic-)Islamic sphere respectively. This volume explores the many dimensions and ramifications of Latin-Arabic entanglement both from macro-historical as well as from micro-historical perspectives. Visions of history marked by the binary opposition of "Islam" and "the West" tend to ignore these important facets of Euromediterranean entanglement, as do historical studies that explain complex transcultural processes without giving attention to their linguistic dimension.